Directing and selecting readings according to Imam Shihab al-Din al-Kurani (d. 893 AH) in his book Ghayat al-Amani - Surat al-Ma’idah as an example (Islamic Sciences Journal, 2024)
ABSTRACTThe research dealt with directing and selecting the abnormal and correct Qur’anic readings in Surat Al-Ma’idah according to the eminent scholar Ahmad bin Ismail Al-Kurani in his interpretation of Ghayat Al-Amani, and clarifying his approach in directing and selecting the readings. In this research, I followed the inductive and analytical approach, by following Al-Kurani’s sayings in his mention of the verses in which he dealt with the readings in Surah Al-Ma'idah, its collection, guidance and study. Relying on books that specialize in Qur’anic recitations, such as books of proofs and others, and books of language and interpretation, in guiding me to the best reading, explaining the reason for choosing one aspect rather than another. The study was divided into an introduction and two topics. The introduction included: introducing Imam Al-Qurani - may God have mercy on him - and the meaning of directing and selecting readings. The first requirement dealt with directing the readings and choosing one reading over others. As for the second requirement, it dealt with directing the readings without choosing one reading over others.
Keywords: Qur’anic readings, guidance, selection, Al-Qurani, table